The effect of home quarantine in light of the Corona pandemic on (positive and negative) thinking among academics at Palestine Ahliya University - Aljamal, Sameer Suleiman; Jaradat, Nasser Mohammed Saud; Al-Zeer, Imad Daoud (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the effect of home quarantine in light of the Corona pandemic on thinking among academics at the Private University of Palestine, and to reveal the existence of differences between the sample members according to variables: (gender, Years of service, college, place of residence). The study followed the descriptive and analytical approach. The sample of the study consisted of (66) faculty members working at the university in all colleges of the university, and the questionnaire was used to collect data. The results of the study indicated that there is an average effect of home quarantine in light of the Corona pandemic on thinking (positive and negative), and the results showed that there are no significant differences in the effect of home quarantine in light of the Corona pandemic on thinking from the point of view of academics, regardless of their gender and duration of service and regardless of the college that They work and where they live. The study came up with several recommendations, the most important of which are: (Urging the faculty members at the university to use the home quarantine to promote positive thinking by transforming the ordeal into a grant, the good and efficient use of time during the home quarantine through the work of research and scientific studies, and the strengthening of cooperation and social communication among colleagues at the university).